Agility and Responsiveness Capabilities: Impact on Supply Chain Performance - Barhmi, Aziz (European Scientific Journal, ESJ, 2019)
This paper focuses on exploring the mediation role of supply chain responsiveness, supply chain agility, and supply chain performance link through a multi-disciplinary review of the relevant research. The systematic literature review aims to provide the basis for formulating a conceptual framework of the relationships. A systematic comprehensive review of the literature on supply chain agility, supply chain responsiveness, and supply chain performance was conducted. The dynamic capabilities perspective literature was also examined to identify the theoretical basis for the contribution of supply chain agility in improving supply chain performance by reconfiguring supply chain responsiveness. The supply chain agility has been mainly explored in the literature with emphasis on the dimensions of the concept. The role of the supply chain agility, as a dynamic capability, in the reconfiguration of the supply chain responsiveness is seen in its quality of operational capability and, consequently, in the improvement of the performance of the supply chain in general.